PELAKSANAAN PENYIDIKAN TINDAK PIDANA PERJUDIAN ADU AYAM DI WILAYAH HUKUM POLISI SEKTOR KERINCI KANAN KABUPATEN SIAK - Simanjuntak, Kalfin Saputra; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Gambling game of chicken is one of the social ills that need to beprevented and mitigated the impact of the implementation is due to thedisruption of public order. As state officials who carry out the functions of lawenforcement, maintenance of public order and safety as well as protection,guidance and community service, police on duty to prevent and mitigate thecrime of gambling. The problem in this thesis is on how the crime of gamblinggame of chicken in the positive law in Indonesia, how the implementation ofthe implementation of the police in tackling crime of gambling, and theconstraints faced by the police in tackling crime of gambling. In positive lawin force in Indonesia, both provided for in Article 303 of the Criminal Codeand the Criminal Code as set out in the Act 7 of 1974 on Gambling Controland Regulation 9 of 1981 on the Implementation of Act 7 of 1974, all of whichdefine gambling as a crime that practice needs to be prevented and addressed.This type of research can be classified in this type of juridicalsociological research, because in this study the authors directly conductresearch on the location or place diteliiti to provide a complete and clearpicture of the problems examined. This research was conducted in thejurisdiction of Police right Kerinci police station, while the population andthe sample is a whole party associated with the problems examined in thisstudy, which used data sources, primary data and secondary data consistingof primary legal materials, secondary and tertiary, data collection techniquesin this study with questionnaires, interviews and literature study.From the research, there are three main problems that can be inferred.First, the implementation of the Crime Investigation Gambling GamesChicken in Sector Police Jurisdiction Right Kerinci enforcement Siak done byfinding the elements of the crime. The second hurdle in the implementation ofthe Crime Investigation Gambling Game Chickens in Kerinci Sector PoliceJurisdiction Right Siak came from law enforcement factors, factor means andfactor of legal awareness. Third, efforts are being made to overcome theobstacles in the implementation of criminal investigations gambling game ofchicken is to seek to do good coordination, working to improve theprofessionalism, establish a harmonious relationship to the community.Advice Author, First, add personnel who have a high quality and quantity,and more serious in handling legal cases that might be able to function properly. Second, the need of holding outreach to the community so thatpeople will understand and be aware of the harmful effects of gambling.Thirdly, For Attorney apparatus and Siak District Court is expected toearnestly implement the rule of law in a criminal offense regarding gamblinggame of chicken and severely condemned.